“This is no Eden:” Three generations of researchers coping with team conflicts in an outstanding research environment - Brodin, Eva; Sewerin, Thomas (Högre utbildning, 2022)
Based on interviews with three generations of professors reflecting upon their development as early career researchers in an outstanding research environment within the STEMfield, this study aimed to explore how they had coped with relationship conflicts in the environment, how this had an impact on their team socialisation, and how their development was framed by their supervisors’ leadership. Using theoretical thematic analysis, we found four conflict responses used by each generation when they were early career researchers. In external competition, they had performed beyond the big bang(s), and when there was a temporary armistice among the senior researchers, they had collaborated for success. Within the environment, they had engaged in quasi-collaboration and navigated in secrecy to evade conflict with their supervisors. Their evasive conflict responses reveal an epistemic living space where the senior researchers’ defensive approach had restricted their scope of learning as doctoral students, and junior scientists had struggled for independence. Seeing that each generation had developed a defensive approach themselves as leaders in their postdoctoral careers, we hold that the real issue in this case is about leadership. Leading doctoral education is not only about leading research, but also about leading education with a caring and systemic approach.